Retail Banking Diagnostic : Treating Customers Fairly in Relation to Transactional Accounts and Fixed Deposits - World Bank Group (World Bank, Washington, DC, 2018)
At the request of the National Treasury of the Republic of South Africa, the World Bank Group (WBG) undertook a Retail Banking Diagnostic focusing on the provision of consumer transactional accounts and fixed deposits by retail banks in South Africa. The aim of the Retail Banking Diagnostic was to identify potential deficiencies from a fair-treatment perspective in banks’ provision of such accounts and deposits, and whether and how any identified major fair-treatment deficiencies could appropriately be addressed through market conduct regulation, having regard to international good practices and the South African market context. A WBG team visited South Africa in April 2017 and undertook discussions to inform the diagnostic with regulators, a range of banks offering consumer transactional accounts and fixed deposits, relevant financial sector ombud schemes, and industry and consumer bodies. Further discussions and inquiries and desk-based research were undertaken following the visit. Except where stated otherwise, the report reflects research undertaken up to September 2017, and it does not cover developments after that time. This report sets out the findings of the diagnostic and provides recommendations for regulatory improvements and related measures for consideration by the South African authorities. Where the report recommends legal measures to address an issue, it is envisaged that these would be implemented either through fair-treatment conduct standards made by the FSCA pursuant to section 106 of the recently passed Financial Sector Regulation Act 2017 (FSR Act) or, in due course, through the Conduct of FinancialInstitutions Bill (COFI Bill) being developed by the National Treasury, and subordinate legislation, such as Standards, to be developed under the resulting COFI Act (referred to collectively in the report as the “COFI/FSR Laws”).